Performance Determinants - Imam, Muhammad; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to examine the influence of integrity, competency and motivation on job satisfaction mediated by work discipline at the Bank Indonesia Representative Office, North Sumatra Province. Production factors are needed to produce human output, but without human labor, commodities and services will not provide the same benefits. The results of this research are as follows: Work Discipline has a positive and significant effect on Job Satisfaction with an original sample value of 0.422 and ap value of 0.000. Integrity has a positive and significant effect on Work Discipline with an original sample value of 0.358 and ap value of 0.000. Integrity has a positive and significant effect on Job Satisfaction with an original sample value of 0.234 and ap value of 0.008. Competence has a positive and significant effect on Work Discipline with an original sample value of 0.234 and ap value of 0.007. Competency has a positive and insignificant effect on Job Satisfaction with an original sample value of 0.044 and ap value of 0.321. Motivation has a positive and significant effect on Work Discipline with an original sample value of 0.394 and ap value of 0.000. Motivation has a positive and significant effect on Job Satisfaction with an original sample value of 0.272 and ap value of 0.002. Integrity has a positive and significant effect on Job Satisfaction through Work Discipline with an original sample value of 0.155 and ap value of 0.003. Competence has a positive and significant effect on Job Satisfaction through Work Discipline with an original sample value of 0.103 and ap value of 0.013. Motivation has a positive and significant effect on Job Satisfaction through Work Discipline with an original sample value of 0.170 and ap value of 0.004.